Uslūb al-Istifhām fī Sūrah Hūd wa Dilālātuhū al-Balāgīyah - Hilaluddin, Zinniirah; Nasir, Mohd Shahrizal (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2023)
The interrogative style of the request constructive styles, and the constructive styles is a branch of the science of meanings (‘ilm al-Ma’ani) in Arabic rhetoric. This research aims to identify the interrogative style and its rhetorical connotations in Surat Hud. The researchers depend on the inductive and analytical approaches in this research. The researchers concluded that the percentage of the interrogative style, there are 23 patterns that contain the use of the interrogative style and 19 verses from Surat Hud, and among them are the negative question, the sarcastic question, the declarative question, the exclamatory question, the rebuking denial question, the command question, the negation question, and the prohibition question.